2022
DOI: 10.1093/ndt/gfac182
|View full text |Cite
|
Sign up to set email alerts
|

Possible role for rareTRPM7variants in patients with hypomagnesaemia with secondary hypocalcaemia

Abstract: Background Hypomagnesemia with secondary hypocalcemia (HSH) is a rare autosomal recessive disorder caused by pathogenic variants in TRPM6, encoding the channel-kinase Transient Receptor Potential Melastatin type 6. Patients have very low serum Mg2+ levels and suffer from muscle cramps and seizures. Despite genetic testing, a subgroup of HSH patients remains without diagnosis. Methods In this study, two families with a HSH phe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…HypoMg has been long associated with increased seizure activities and epilepsy 1 4 , 37 . We have found that a low-Mg diet induces seizures and death, with female mice being more susceptible than males 11 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…HypoMg has been long associated with increased seizure activities and epilepsy 1 4 , 37 . We have found that a low-Mg diet induces seizures and death, with female mice being more susceptible than males 11 .…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in both TRPM6 and TRPM7 have been associated with HypoMg and seizures 2 , 4 , 5 . Moreover, Mg supplementation can prevent these seizures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Strikingly, the mortality rate of the pups can be decreased if dams are supplemented with Zn during pregnancy. Recently, human patients with rare mutations in Trpm7 were found in patients with hereditary hypomagnesemia with secondary hypocalcemia [427]. Patients suffered from seizures and muscle cramps due to magnesium deficiency and episodes of hypocalcemia.…”
Section: Trpm7: a New Player In Zinc Homeostasismentioning
confidence: 99%
“…Gitelman syndrome, arising from SLC12A3 mutations, disrupts magnesium reabsorption, resulting in hypomagnesemia and hypercalciuria [ 3 ]. Hypocalciuric hypomagnesemia, attributed to mutations in the thick ascending limb of Henle, leads to hypercalciuric hypomagnesemia [ 4 ]. Furthermore, epilepsy, ataxia, sensorineural deafness (EAST) syndrome, stemming from KCNJ10 mutations, culminates in hypomagnesemia due to impaired Kir4.1 potassium channel function [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%